Violence and Masculinity in Mexico - Ricardo Rodríguez Luna (Oñati Socio-Legal Series)
This research analyzes the possible links between gender, age and violence in the homicides that take place in Mexico. Based on statistical records, the degree of criminal responsibility and victimization of young men in this crime is outlined. Secondly, the way in which different criminology perspectives have explained the aforementioned problem is analyzed, specifically, how they have taken into account the male gender and age; about it, three different approaches are presented: the positivist, sociological and sexual difference. To conclude, from this last perspective, the preventive strategies that the Mexican government has set in motion to prevent excessive number of male deaths due to homicide are questioned.